Fingerprint enhancement using modified short-time fourier transform - Chopra, Jyotika; Kumar, Amod; Marwaha, Anupma; Marwaha, Sanjay (International Journal of Engineering and Technology, 2018)
In this paper, a Modified Short-time Fourier Transform (M-STFT) fingerprint enhancement technique for non-stationary ridges has been proposed. It improves the local section of image as the fingerprint ridges fade or change with the passage of time. Freely available database (FVC2002 DB3) was used to evaluate the method. To choose the appropriate process window, various experiments on a subset of database were performed. The proposed approach based on the use of Tukey window analyses the transient data more effectively compared with other windows. The non-stationary nature of images are more efficiently enhanced using Tukey window. This scheme not only promises better fingerprint enhancement but also results in lesser computational cost than the existing methods. Â Â Â